Views from the top and below: an exploration of what intersectionality brings to sectoral research - Mooney, Shelagh; Ryan, Irene (Institute for Intersectionality Research and Policy, Simon Fraser University, Vancouver, 2014)
The impact of gender and other embodied diversity markers is rarely mentioned in the burgeoning literature on careers. In contrast, feminist scholarship recognises the multiple ways gender, race/ethnicity, age, class and/or other diversity markers influence individual career choices. The research approach that examines the interaction of multiple categories of difference is known as intersectionality, and although the ‘right way’ to carry out intersectional research remains the subject of intense debate, scholars concur that it is complex and “messy” (Dhamoon 2011, 240). This article focuses on the female dominated hotel sector in Aotearoa New Zealand. An intersectional multi-level analysis used memory-work and semi-structured interviews to explore the career experiences of long-term hospitality workers. At career entry, career consolidation and career arrival phases, the multiple ways privilege and disadvantage intersect are considered. Our overall intent is to highlight the extent that age, gender, ethnicity and class context, shape career choices in hotels.
Keywords: Age; Gender; Class; Ethnicity; Privilege; Penalty; Intersectionality